Analysing equipment needs for hotel laundry business initiation: A case study of Teaching Factory (TeFa) Integrated Hotel - Milawaty, Milawaty; Kamiliyah NH, Uystka Hikmatul; Utami, Lely Dian; Dzulkifli, Muhammad; Azizah, Safira Salsa Bila Fitrotin; Samsudin, Asep (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2024)
As a vocational college, Politeknik Negeri Jember (Polije) has developed teaching factories, or TeFa, as one manifestation of ‘learning by doing’ to provide skilled graduates for the industrial world. TeFa Integrated Hotel, one of 29 Teaching Factories established by Polije, is gearing up to give the students a small-size hospitality industry simulation. Thus, it intends to improve services by one of which is initiating a hotel laundry business. This research aims to analyse the equipment needed to initiate a laundry business at the TeFa Integrated Hotel. This laundry business is essential for the TeFa to fulfil the needs of customers and its housekeeping section to suppress the operational costs. This research applied a descriptive-qualitative method by collecting data through in-depth interviews and Focus Group Discussions (FDG). The results showed that to start a laundry business, some equipment must be available, including work equipment such as washing machines, dryers, irons, and ironing boards, as well as consumable equipment such as detergent, softener, bleach, acids, and alkalis. For a small-sized hotel laundry, the work equipment standard that must be met includes the size of the washing machine, which is usually equipped with a drying machine between 8-20 Kg adjusted to the room quota and variety of customers. As equipment is the main supporter in running a business, this research can be impactful in determining the business's success in the future. Additionally, any service improvements made by TeFa Integrated Hotel will further support Polije in providing the best graduates to the industry.